ANALYSIS OF PUBLIC SATISFACTION WITH THE APPLICATION OF RAPID POPULATION AND CIVIL REGISTRATION SERVICES (PACEDUKCAPIL) K O TA JAYAPURA DURING THE PANDEMIC COVID-19 - Yasir Attamimi; Hesti Murwaniputri; Aprianto La'lang Kuddy (INFOKUM, 2022)
This research was motivated by the occurrence of the Corona Virus Disease 2019 attack or abbreviated as COVID-19 which made the Government of Indonesia take policies and strategic steps by lockdown and social distancing in order to break the chain of spread of COVID-19, In the dimension of public services, some offices limit their service operating hours, implement health protocols such as the obligation to use gloves, Masks, hand sanitizers to maintain distance between employees and the community, some are even forced to furlough their employees and close temporarily. The type of research used in this country is descriptive research, According to Notoatmodjo (2012), descriptive research is a research method carried out with the main aim of making an objective picture or description of a situation. This research was carried out at the Office of the Population and Civil Registration Office of K ota Jayapura which is very muchin the officeand Balai K o ta, Entr o p, South Jayapura, Kota Jayapura. Where the population or unit of analysis in this study is the entire community that uses the rapidpopulation and civil registration service (PACEDUKCAPIL) Kota Jayapura on the time of August 2, 2021 (awa l the use of the applicationlikasi) until August 2, 2022 which berjum lah 53.070 Orang. Sampling was carried out using proportionate stratified random sampling techniques using formulas from Krejcie and Morgan, resulting in 381 responden. The results of this study show a Community Satisfaction Index (IKM) score with an Index number of: 82.00, it can be concluded that the performance of the Population and Civil Registration Office that performs services to the community using the population and civil registration fast service application (PACEDUKCAPIL) is in service quality B with the GOOD category, because it is in the conversion interval value of Community Satisfaction Index 76.61 - 88.30.